The reconcile methode on contradicted hadith | جمع التعارض في مختلف الحديث - Hasan Basri Salim (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2008)
Some people think that contradicted ahadithcannot be reconciled or unified. All theahadits which are seen textually contradictedwith the others, in fact, are not, because theyare all revelations (wahy) from Allah to theprophet Muhammad SAW. Muslim juristsand scholars have tried to find out methodshaw to reconcile the ahadith that are seentextually to be contradictory with others.